3D Printing of Bone Grafts for Cleft Alveolar Osteoplasty – In vivo Evaluation in a Preclinical Model - Korn, Paula; Ahlfeld, Tilman; Lahmeyer, Franziska; Kilian, David; Sembdner, Philipp; Stelzer, Ralph; Pradel, Winnie; Franke, Adrian; Rauner, Martina; Range, Ursula; Stadlinger, Bernd; Lode, Anja; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
One of the most common hereditary craniofacial anomalies in humans are cleft lips and cleft alveolar bone with or without cleft palate. Current clinical practice, the augmentation of the persisting alveolar bone defect by using autologous bone grafts, has considerable disadvantages motivating to an intensive search for alternatives. We developed a novel therapy concept based on 3D printing of biodegradable calcium phosphate-based materials and integration of osteogenic cells allowing fabrication of patient-specific, tissue-engineered bone grafts. Objective of the present study was the in vivo evaluation of implants in a rat alveolar cleft model. Scaffolds were designed according to the defect`s geometry with two different pore designs (60° and 30° rotated layer orientation) and produced by extrusion-based 3D plotting of a pasty calcium phosphate cement. The cement fitted into the artificial bone defect in the palate of adult Lewis rats, showing a good support. Half of the scaffolds were colonized with rat mesenchymal stromal cells (rMSC) prior to implantation. After 6 and 12 weeks, remaining defect width and bone formation were quantified histologically and by microCT. The results revealed excellent osteoconductive properties of the scaffolds, a significant influence of the pore geometry (60°>30°), but no enhanced defect healing by pre-colonization with rMSC.